2006
DOI: 10.1007/s10499-005-9039-5
|View full text |Cite
|
Sign up to set email alerts
|

Yields of great scallop, Pecten maximus, larvae in a commercial flow-through rearing system in Norway

Abstract: Survival, growth and yield of competent great scallop (Pecten maximus) larvae were investigated during a full production season in a commercial hatchery in western Norway. Broodstock were collected from natural scallop beds and 12 groups were induced to spawn during the period December 2002 to July 2003. Larvae were reared on a large scale in 36 flow-through tanks (3500 l) at 17±1°C and continuously fed a mixture of five algal species produced in an indoor continuous-flow system. Large variations in larval per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
61
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 39 publications
6
61
1
Order By: Relevance
“…Although the results showed that many FAs varied between replicates and over time, the production of the essential PUFAs increased. Considering the total microalgal production of the essential PUFAs in this experiment, a stable supply of all the essential PUFAs to the scallop larvae and spat was secured at a ratio of 1:1:1 of Isochrysis sp., P. lutheri and C. muelleri, similar to combinations used in scallop hatchery by Magnesen et al (2006). Improvements to be considered in order to increase PUFA production further are lower pH and increase light penetration, particularly in the Isochrysis sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the results showed that many FAs varied between replicates and over time, the production of the essential PUFAs increased. Considering the total microalgal production of the essential PUFAs in this experiment, a stable supply of all the essential PUFAs to the scallop larvae and spat was secured at a ratio of 1:1:1 of Isochrysis sp., P. lutheri and C. muelleri, similar to combinations used in scallop hatchery by Magnesen et al (2006). Improvements to be considered in order to increase PUFA production further are lower pH and increase light penetration, particularly in the Isochrysis sp.…”
Section: Discussionmentioning
confidence: 99%
“…Three species, Isochrysis sp., P. lutheri and C. muelleri, widely used as feed in bivalve hatcheries because of their nutritional profile, were grown in commercial scale (e.g. Magnesen et al 2006). The variation of FAs in the algal production system were analysed between replicate bags over time.…”
Section: Introductionmentioning
confidence: 99%
“…However, the overuse of antibiotics in treatment of mollusk aquaculture may contribute to an increase in the level of antimicrobial resistance (Mechri et al 2013(Mechri et al , 2015. The introduction of a flowthrough system instead of closed-circuit water system in larval rearing tanks eliminated the use of antibiotics by improving water quality (Southgate and Ito 1998;Magnesen et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These authors also revealed that the use of FTS with constant flows of highquality water and a daily cleaning of the sieve clogs facilitated the circulation in the rearing tank and removal of metabolic waste products providing favorable conditions for larval development. Several studies suggested an association between the stocking density and the water exchange rate (Magnesen et al 2006;Rico-Villa et al 2008). Furthermore, Andersen et al (2000) and Sarkis et al (2006) reported a reduction in growth performance at high stocking density when they reared scallop (Pecten maximus) and oyster (C. gigas) larvae in FTS.…”
Section: Discussionmentioning
confidence: 99%
“…Twentyfour hours later, the incubator tank was drained onto a 35 µm sieve and D-shaped larvae were concentrated in a 5 L graduated cylinder. D-shaped larvae were counted (3 × 20 µl) and then reared in a through-flow culture system (Magnesen et al 2006;Rico-Villa et al 2008;Sarkis et al 2006) in 4 replicates. D-shaped larvae were fed using three tropical species of micro-algae: Isochrysis clone T-Iso, Chaetoceros minus and Chaetoceros gracilis.…”
Section: Demonstration Of Hatchery Applicationmentioning
confidence: 99%